Answer:
(a) [tex]\vec{R}= 4.83\ m\ \hat{i}+1.47\ m\ \hat{j}[/tex]
(b) (5.05 m, 16.93 degrees wrt x-axis)
Explanation:
Given:
Let us first fond out vector D and E in their rectangular form.
[tex]\vec{D} = (3\cos 315^\circ\ \hat{i}+3\sin 315^\circ\ \hat{j})\ m\\\Rightarrow \vec{D} = (2.12\ \hat{i}-2.12\ \hat{j})\ m\\[/tex]
Similarly,
[tex]\vec{E} = (4.5\cos 53^\circ\ \hat{i}+4.5\sin 53^\circ\ \hat{j})\ m\\\Rightarrow \vec{D} = (2.71\ \hat{i}+3.59\ \hat{j})\ m\\\because \vec{R}=\vec{D}+\vec{E}\\\therefore \vec{R} = (2.12\ \hat{i}-2.12\ \hat{j})\ m+(2.71\ \hat{i}+3.59\ \hat{j})\ m\\\Rightarrow \vec{R} = (4.83\ \hat{i}+1.47\ \hat{j})\ m[/tex]
Part (a):
We can write the resultant vector R as below:
[tex]\vec{R} = (4.83\ \hat{i}+1.47\ \hat{j})\ m[/tex]
Part (b):
[tex]Magnitude\ of\ resultant = \sqrt{4.83^2+1.47^2}\ m = 5.05\ m\\\textrm{Direction in angle with the x-axis} = \theta = \tan^{-1}(\dfrac{1.47}{4.83})= 16.93^\circ[/tex]
Since both the components of the resultant lie on the positive x and y axes. So, the resultant makes an acute angle with the positive x-axis.
So, R = (5.05 m, 16.93 degrees wrt x-axis)